2000
DOI: 10.1139/e99-114
|View full text |Cite
|
Sign up to set email alerts
|

Hurricanes Pauline and Nora rainwater chemical composition

Abstract: Rainwater from hurricanes Pauline and Nora was sampled for chemical analysis at the Pacific Coast of Mexico. Rainwater sampling under extreme conditions presents a unique opportunity to study oceanic rain chemical composition. An excess sulphate ((SO2–4)xs) as low as 0% was measured near the centre of hurricane Pauline in Huatulco Bays. Another remarkable result was obtained in another rainwater sample of Pauline rain bands with a total SO2–4 concentration below the detection limit. Also, Na+ and Cl– concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…This behavior has been reported for other authors, who have found an abrupt increase of sea spray droplets when wind speed increases as hurricanes approach the coast. This was also observed by Padilla et al [25] in Huatulco Bay and Manzanillo, Colima in Mexico. Cerón and collaborators [21] found high levels of sodium and chloride in Monterrey after the passage of the Hurricane "Alex" in 2010.…”
Section: Resultssupporting
confidence: 82%
“…This behavior has been reported for other authors, who have found an abrupt increase of sea spray droplets when wind speed increases as hurricanes approach the coast. This was also observed by Padilla et al [25] in Huatulco Bay and Manzanillo, Colima in Mexico. Cerón and collaborators [21] found high levels of sodium and chloride in Monterrey after the passage of the Hurricane "Alex" in 2010.…”
Section: Resultssupporting
confidence: 82%
“…The highest values were observed during August, when hurricane "Ernesto" arrived to the island. It is agree with reported by Padilla et al [11], where a relationship between hurricanes ("Paulina" and "Nora") and high pH levels was reported.…”
Section: Ionic Concentrationssupporting
confidence: 93%
“…High levels of sulfate excess were present in samples collected during the study period, suggesting the influence of the emissions from power plants located upwind the sampling site; this percentage is in agreement with the sulfate excess reported by Padilla et al [5] in rainwater samples in this site.…”
Section: Marine Aerosol Contributionsupporting
confidence: 91%
“…Figure 1 and Table 1 show the geographical position and main characteristics of the sampling site. High excess sulfate has been reported in rainwater samples in Manzanillo [5], and it has been concluded that this sul- fate excess had a predominant anthropogenic background origin. This sulfate excess can be explained from two sources: the long-range transport from Guadalajara City, because Manzanillo is located downwind from this important urban and industrialized area (trade winds blow from this direction during the summer); and two fossilfueled power plants that operate continuously, located in this site.…”
Section: Sampling Site Descriptionmentioning
confidence: 99%